Enhancing clean sport behaviour at school: evaluation of the effectiveness of positive education intervention program in Malaysian adolescent athletes - Abdullah, Haslinda; Azmi, Syasya Firzana; Ma’rof, Aini Azeqa; Soh, Kim Geok; Zarehmohzzabieh, Zeinab; Mohammed Shaffril, Hayrol Azril (UniKL Royal College of Medicine Perak, 2024)
Introduction: Doping endangers athletes' health and degrades sports by substituting fair competition with an inflated perception of power. Young athletes are particularly prone to hazardous behaviours when lack a strong ethical grounding. This study provides a novel positive education intervention designed to encourage players to engage in clean sport behaviour. With increased worries about doping and unethical behaviours, the intervention focuses on fostering a culture of integrity, respect, and fair play, as well as promoting the value of competition and anti-doping principles. Methodology: Using the PERMA Model (Seligman, 2018), the intervention delivers training modules as a comic book series that emphasises the dangers of doping and promotes clean sport ideals. The study involved 40 adolescent’s athletes from the Malaysian National Sport School and used a pre-test post-test control group design. The intervention was administered to the experimental group, but not to the control group. Results: The experimental group demonstrated a better comprehension of anti-doping rules, more ethical decision-making abilities, and a greater dedication to clean sport. In addition, compared to the control group, participants demonstrated improved attitudes towards sport ideals and understanding of doping. Conclusions: The findings show that a PERMA-based positive education intervention effectively promotes clean sport behaviour, improves anti-doping awareness, and develops ethical decision-making among young athletes.